The Role of Impulsive Buying in Shaping Gen Z’s Blind Box Repurchase Behavior - Alvi Nuraini; Irmawan Rahyadi (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: Empirical studies on blind box consumption among Generation Z in Indonesia remain limited, particularly regarding the combined roles of curiosity, product variety, and Fear of Missing Out (FoMO) in shaping impulsive buying and repurchase intention. Objective: This study aims to examine the effects of curiosity, product variety, and FoMO on repurchase intention, with impulsive buying as a mediating variable among Generation Z blind box consumers in Jakarta. Methods: A quantitative research design was employed using non-probability purposive sampling targeting Generation Z consumers in Jakarta who had prior blind box purchasing experience. A total of 413 valid responses were collected via an online questionnaire, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results: The findings indicate that FoMO exerts a significant indirect influence on repurchase intention via impulsive buying (t = 2.611 > 1.96). These results underscore the importance of psychological triggers in the blind box industry and provide valuable insights for marketers in leveraging curiosity and social influence to enhance consumer retention. Conclusion: This study confirms that curiosity, product variety, and FoMO positively influence impulsive buying, which in turn significantly predicts repurchase intention among Generation Z blind box consumers in Jakarta. These findings offer actionable implications for marketers seeking to leverage psychological triggers and experiential retail strategies to sustain consumer loyalty.